A survey of hot flow anomalies at Venus. Issue 2 (18th February 2014) - Collinson, G. A.; Sibeck, D. G.; Masters, A.; Shane, N.; Zhang, T. L.; Fedorov, A.; Barabash, S.; Coates, A. J.; Moore, T. E.; Slavin, J. A.; Uritsky, V. M.; Boardsen, S.; et al.
<x xml:space="preserve">Abstract</x> We present the first survey of hot flow anomalies (HFAs) at the bow shock of Venus, expanding on our recent initial case study. A 3.06 sol (774 Earth day) survey of Venus Express magnetometer, ion spectrometer, and electron spectrometer data was undertaken in order to identify Cytherian HFAs. Seven events were discovered, corresponding to a statistical frequency ≈1.2±0.8 per day, approximately the same rate as at the Earth. All seven HFAs were centered on a discontinuity in the solar wind, with inward pointing motional electric fields on at least one side, and exhibited electron and ion perturbations consistent with heating. For one event the calculation of continuous electron moments is possible, revealing that electron temperature increased from ≈2×105 K to 8×105 K in the HFA core (comparable to terrestrial and Kronian HFA observations), and density increased from ≈1 cm−3 to 2→2.5 cm−3 in the bounding compression regions. Cytherian HFAs were found to be physically smaller (0.4→1.7 Venus radii (RV)) than their terrestrial or Kronian counterparts, although are much larger when compared to the overall size of the system (≈130% of the subsolar bow shock distance), and occur very close (1.5→3.0RV) to the planet. Thus, we hypothesize that HFAs have a much more dominant role in the dynamics of the induced magnetosphere of Venus relative to the magnetospheres of magnetized planets.